THE REGULATION OF PINOCYTOSIS IN MOUSE MACROPHAGES : II. FACTORS INDUCING VESICLE FORMATION - Cohn, Zanvil A. (The Rockefeller University Press, 1967)
The pinocytosis-inducing effect of a number of molecular species was studied in cultures of mouse macrophages. Agents were added to a basal medium containing 1% NBCS-No. 199 and allowed to interact with cells for 150 min. Vesicle counts were then performed and compared to control cells in the basal medium. Certain proteins, i.e. albumin and fetuin, with isoelectric points of five and below were found to be potent stimulators of vesicle formation. Basic proteins including lysozyme, histone, and protamine had little influence at sublethal concentrations. The pinocytosis-stimulating activity of bovine plasma albumin could be markedly depressed by removal of bound fatty acids. The addition of either oleic or linoleic acid to de-fatted albumin restored its inducing properties to initial levels. The activity of fetuin could be abolished by either mild acid hydrolysis or neuraminidase digestion. Both procedures removed the majority of the sialic acid content of fetuin. The D and L isomers of polyglutamic acid were found to produce a marked increase in pinosome production. In contrast, poly-DL-lysine was not effective. Neutral and basic amino acids were without significant effect on pinocytosis, whereas aspartic and glutamic acids were stimulatory. The amides of glutamic and aspartic acid did not induce pinocytosis. The unnatural D isomers of glutamic, aspartic, leucine, and phenylalanine inhibited pinocytosis. The inhibition by D-glutamic acid could be reversed with the L isomer. A number of acid mucopolysaccharides, including heparin, hyaluronic acid, and chondroitin sulfate, were excellent inducers. High molecular weight dextran was without significant stimulatory effect whereas dextran sulfate was very active. Both desoxyribonucleic acid and ribonucleic acid enhanced pinosome formation. A number of low molecular weight anions including N-acetylneuraminic acid were found to enhance vesicle formation. In general, anionic molecules were better inducers than either neutral or cationic species. The minimum effective dose of macroanions was a function of molecular weight and their activity appeared unrelated to specific chemical groupings.